1989
DOI: 10.1139/t89-028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple contaminant migration on diffusion and adsorption of some domestic waste contaminants in a natural clayey soil

Abstract: This paper describes laboratory model tests involving the placement of domestic landfill leachate on top of a layer of saturated undisturbed clayey soil and allowing chemical constituents to migrate into the soil by diffusion only. During the testing period (15 days), samples from the overlying leachate were regularly collected and analyzed for the chemical constituents of interest (i.e., Cl−, Na+, K+, Mg++, and Ca++). At the end of the test, the soil layer was sectioned to determine the pore-water and adsorbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
10

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 4 publications
1
33
1
10
Order By: Relevance
“…Under these conditions, predicted times for pollutant breaching a clay barrier are several hundred years. Field trials, however, have shown that some small molecules do not adhere to this behavior and move rapidly through soils (Johnson et al 1989;Goodall and Quigley 1977;Quigley et al 1987;Barone et al 1989;Crooks and Quigley 1989). As a result the mode of diffusive transport of solutes through clay films is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, predicted times for pollutant breaching a clay barrier are several hundred years. Field trials, however, have shown that some small molecules do not adhere to this behavior and move rapidly through soils (Johnson et al 1989;Goodall and Quigley 1977;Quigley et al 1987;Barone et al 1989;Crooks and Quigley 1989). As a result the mode of diffusive transport of solutes through clay films is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of pollutant transport parameters based on laboratory tests such as column, diffusion and batch equilibrium tests are also important in the more detailed phases of geoenvironmental investigations (Freeze & Cherry, 1979;Rowe et al, 1988;Barone et al, 1989;Shackelford & Daniel, 1991;Yong et al, 1992;Shackelford, 1993;ong, 2001). These laboratory tests can be conducted with the objective of a better interpretation of the in-situ test results, and for a numerical modeling performance, using a good conceptual model definition for the problem.…”
Section: Pollutant Transport Parametersmentioning
confidence: 99%
“…Diffusion tests followed the procedure described by Barone, et al [1]. The specimens were compacted directly in the moulds, and saturated by capillarity and seepage.…”
Section: Diffusion Testsmentioning
confidence: 99%